2014
DOI: 10.3233/jvr-140708
|View full text |Cite
|
Sign up to set email alerts
|

Promising best practices that lead to employment in vocational rehabilitation: Findings from a four-state multiple case study

Abstract: The state-federal vocational rehabilitation (VR) program has been challenged to demonstrate the effectiveness of VR services provided to eligible consumers. State-federal VR agencies are under pressure to develop a foundation of evidence-based practices that lead to competitive employment outcomes for people with disabilities. This article provides a qualitative analysis of the organization structural elements and service delivery practices related to the provision of effective best practices that enhance empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…VR practices can be categorized into two broad thematic areas: "organizational practices" which are system-level changes that foster innovative practices; and "promising service delivery practices" which facilitate employment outcomes at multiple levels across agencies and employers through use of partnerships, certification, and trainings (Del Valle et al, 2014;Leahy et al, 2014). Nearly all autism-related activities across state WIOA plans concerned service delivery practices.…”
Section: Discussionmentioning
confidence: 99%
“…VR practices can be categorized into two broad thematic areas: "organizational practices" which are system-level changes that foster innovative practices; and "promising service delivery practices" which facilitate employment outcomes at multiple levels across agencies and employers through use of partnerships, certification, and trainings (Del Valle et al, 2014;Leahy et al, 2014). Nearly all autism-related activities across state WIOA plans concerned service delivery practices.…”
Section: Discussionmentioning
confidence: 99%
“…Second, with the 571% increase in the number of individuals with ASD seeking services through VR, it is critical that those tasked with helping individuals get a job (e.g., VR counselors, job developers), as well as employers and natural supports understand the characteristics of ASD and how they manifest in individuals (Alverson et al, 2015). Valle et al (2014) found specialized VR case loads to be an effective strategy for supporting individuals with ASD. Although VR counselors may not have a single-focused caseload, developing expertise in ASD may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…One way to improve research utilization is through improved knowledge translation processes (Chan et al, 2009). For example, Del Valle et al (2014) identified promising practices and EBPs that have already been used by counselors, including motivational interviewing, individual placement and support model of supported employment, secondary transition services, workplace socialization skills training, workplace support services, and benefits counseling. Leahy et al (2014) suggested that practices could be implemented and made readily available to counselors by the state VR agencies through technical assistance, consultation, and training opportunities.…”
Section: Discussionmentioning
confidence: 99%